ANALISIS PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KEPUASAN KERJA SEBAGAI VARIABEL PEMEDIASI PADA RUMAH SAKIT DKT GOMBONG - Indah Rohyani (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2017)
ABSTRACT This study aimed to examine the effect of directly or indirectly from variables organizational culture, commitment to job satisfaction and OCB. Research questionnaire distributed to the entire population of 42 employees Hospital DKT Gombong Kebumen and processed by using SPSS 18. Based on the survey results revealed positive affect directly culture and commitment affect to satisfaction. This is also demonstrated through the satisfaction;organizational culture and commitment positive affect influential to OCB.